Electrons and phonons the theory of transport phenomena in solids - Ziman, J. M. (John M.), 1925-2005.; Oxford eBooks (Oxford : Clarendon, 1960)
Electrons and Phonons represents a study of the theory of electrical and thermal conduction in metals, semiconductors, and insulators. The basic ideas of crystal lattice dynamics and electron zone structure are developed from first principles.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Phonons; Electrons; Transport theory; Electronic books